IT AS AN EFFECTIVE TOOL IN THE MODERN SYSTEM OF EDUCATION - Elena N. Zvereva; Olga V. Haritonova (Статистика и экономика, 2016)
This paper aims to consider the importance of informationtechnology technologies in the modern educational process.This new model of education involves extensive use of IT in various forms: a test of the shell, training programs andplatforms, electronic resources, the Internet. This article also emphasizes relevance of transition to new forms of educationbased on the principles of the use of computer technologies.The attention is also paid to test control as evaluation of quality of knowledge in a modern format that enables to test thenumerous audience remotely through technology. The authors showed the importance of electronic testing for the developmentof analytical skills of students on the example of analysis of theFederal Internet-examination.